2021
DOI: 10.1111/tpj.15360
|View full text |Cite
|
Sign up to set email alerts
|

Integration of electric, calcium, reactive oxygen species and hydraulic signals during rapid systemic signaling in plants

Abstract: The sensing of abiotic stress, mechanical injury or pathogen attack by a single plant tissue results in the activation of systemic signals that travel from the affected tissue to the entire plant. This process is essential for plant survival during stress and is termed systemic signaling. Among the different signals triggered during this process are calcium, electric, reactive oxygen species and hydraulic signals. These are thought to propagate at rapid rates through the plant vascular bundles and to regulate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 66 publications
3
81
0
Order By: Relevance
“…It appears, then, that increasing S and GSH within a plant could reduce StHD severity in two ways, by increasing Aschelation and by increasing ROS scavenging. Other elements with known roles in induction of ROS scavenging include Si (Kim et al, 2017), Ca (Fichman and Mittler, 2021), and Cu (Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It appears, then, that increasing S and GSH within a plant could reduce StHD severity in two ways, by increasing Aschelation and by increasing ROS scavenging. Other elements with known roles in induction of ROS scavenging include Si (Kim et al, 2017), Ca (Fichman and Mittler, 2021), and Cu (Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Upon sensing of H 2 O 2 , HPCA1 was found to trigger the accumulation of calcium in the cytosol (Wu et al, 2020). This process could activate another type of cell-to-cell signaling pathway termed the ‘calcium wave’ (dependent on the function of the calcium channels glutamate-like receptor 3.3 and 3.6; GLRs; Evans et al, 2016; Toyota et al, 2018; Shao et al, 2020; Fichman and Mittler, 2021a). To determine whether HPCA1 is also required for systemic cell-to-cell calcium signals, we subjected a single leaf of WT, hpca1-1, and hpca1-2 plants to the same HL stress treatment described above and used Fluo-4-AM as a probe in our live imaging platform (Fichman and Mittler, 2021a) to measure changes in cytosolic calcium levels in local and systemic leaves over a period of 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic cell-to-cell calcium and ROS signals were previously proposed to be linked with another type of cell-to-cell signaling, termed the ‘electric wave’ (a rapid depolarization of the plasma membrane, also dependent on the function of GLRs; Mousavi et al, 2013; Nguyen et al, 2018; Farmer et al, 2020; Fichman and Mittler, 2021a). To determine whether HPCA1 is also required for systemic cell-to-cell membrane depolarization signals, we subjected a single leaf of WT, hpca1-1, and hpca1-2 plants to the same HL stress treatment described above and used DiBAC 4 (3) as a probe in our live imaging platform (Fichman and Mittler, 2021a) to measure these changes in local and systemic leaves over a period of 30 min. Interestingly, while the systemic cell-to-cell calcium and ROS signals were suppressed in the hpca1 mutants (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transient change of the cytoplasmic calcium concentration ([Ca 2+ ] cyt ) is one of the earliest events in plant cells upon pathogen recognition, and many studies applying different calcium indicators reported on distinct [Ca 2+ ] cyt patterns in response to PAMPs, e.g., bacterial flg22 ( Ranf et al, 2011 ; Maintz et al, 2014 ; Seybold et al, 2014 ; Thor and Peiter, 2014 ; Keinath et al, 2015 ; Aldon et al, 2018 ; Tian et al, 2020 ). Furthermore, calcium and calcium signaling being instrumental during defense signal propagation from a local attacked site to systemic parts of a plant has been observed as a spread of a calcium signals through the plant along the vasculature and beyond ( Romeis and Herde, 2014 ; Kiep et al, 2015 ; Nguyen et al, 2018 ; Toyota et al, 2018 ; Shao et al, 2020 ; Fichman and Mittler, 2021 ). However, it is unknown whether [Ca 2+ ] cyt changes contribute to SAR.…”
Section: Introductionmentioning
confidence: 99%